2023
DOI: 10.1093/aesa/saad015
|View full text |Cite
|
Sign up to set email alerts
|

Description of Neoseiulus hexaporus sp. nov. and a redescription of Neoseiulus mumai (Acari: Mesostigmata: Phytoseiidae) from Florida citrus groves

Abstract: Predatory mites are effective natural enemies of small arthropods, including pest mites and insects, which provide biological control of several crop pests worldwide. The family Phytoseiidae (Acari: Mesostigmata) is a diverse group of predators found in cultivated crops and other habitats containing natural vegetation. Although some phytoseiid species are commercialized and widely used in biological control programs, the determination of natural populations and identification of the species is a vital first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(91 reference statements)
1
0
0
Order By: Relevance
“…Proprioseiopsis mexicanus was dominant in the ground cover. It was previously reported as an abundant species in the French West Indies and Alabama citrus orchards(Fadamiro et al 2009;Kreiter et al 2018; Mailloux et Moreover, all Neuseiulus species identified in our study were encountered in the ground cover except for N. marinellus which was also sampled from leaf litter(Demard et al 2021;Döker et al 2023). This confirms that Neoseiulus are generalist predators inhabiting soil and respectively Childers and Denmark (2011).…”
supporting
confidence: 87%
“…Proprioseiopsis mexicanus was dominant in the ground cover. It was previously reported as an abundant species in the French West Indies and Alabama citrus orchards(Fadamiro et al 2009;Kreiter et al 2018; Mailloux et Moreover, all Neuseiulus species identified in our study were encountered in the ground cover except for N. marinellus which was also sampled from leaf litter(Demard et al 2021;Döker et al 2023). This confirms that Neoseiulus are generalist predators inhabiting soil and respectively Childers and Denmark (2011).…”
supporting
confidence: 87%